A new species of endoparasitic isopod, Portunion sinensis sp. nov. (Isopoda: Entoniscidae), found in the mud crab Scylla paramamosain in China - Huang, Teng; Ma, Xiaowan; Zhong, Shengping; Chen, Xuyang; Yang, Dong; Guo, Jiasen; Huang, Lixing; Li, Wenhong; Pengsakul, Theerakamol; Qiao, Ying (Frontiers in Marine Science, 2025)
Portunion (Isopoda, Epicaridea, Entoniscidae) is an extremely rare endoparasitic isopod genus that is found mainly in the blood cavity of decapod crustaceans, such as true crabs and hermit crabs. The mud crab (Scylla paramamosain) is one of the most economically important crab species in south China and Asia. In this study, we identified a new endoparasitic isopod species, Portunion sinensis sp. nov., from the hemocoel of S. paramamosain. Portunion sinensis sp. nov. is similar to Portunion conformis in having the anterior vertical to thorax, the posterior directed backwards for Female’s ventral processes. However, the new species can be distinguished from Portunion conformis by the rudimentary abdominal spines present on segment III-IV in males. Herein we describe a detailed morphological description of this new species and conduct an extensive comparison with related species. This study marks the first description Portunion sinensis sp. nov. of an endoparasitic isopod species found in Scylla paramamosain in China. The findings expand the known biodiversity of parasitic isopods and contribute to understanding the host-parasite associations within this commercially significant crab species in the region.